THE EFFECTIVENESS OF USING BOARD RACE GAME TO ENHANCE THE STUDENTS’ VOCABULARY MASTERY AT SMPN 8 DONGGO SATU ATAP - Nurdina; St. Asriati AM; Saiful (FKIP Unismuh Makassar, 2021)
This research aimed to enhance students’ vocabulary mastery at SMPN 8 Donggo Satu Atap by using board race game. The researcher used pre-experimental research where the data gained from the multiple choice test. The population of the research was the eighth grade of SMPN 8 Donggo Satu Atap in the academic year 2020/2021. The sample was taken by using purposive sampling technique and there were 80 students as population and 20 students as sample. The result presented that the mean score of students’ vocabulary mastery pre-test in the term verb was 45.25 become 78.5 in post-test with 73.48% improvement. Then, the mean score in term of adverb was 42.75 in the pre-test become 69 in the post test with 61.40% improvement. The t-test analysis presented that by applying 0.05 level of significant with the 19 degree freedom (df=20-1), t-test in the form of verb and adverb in vocabulary was greater than t-table which were 11.62>2.093 and 13.72>2.093. It means that, board race game has significant effect toward students’ vocabulary mastery in the term of verb and adverb.